DISINFLATION, INEQUALITY, AND WELFARE IN A TANK MODEL. (17th December 2019) - Tirelli, Patrizio; Ferrara, Maria
Abstract : We investigate the redistributive and welfare effects of disinflation in a two‐agent New Keynesian model characterized by limited asset market participation and wealth inequality. We highlight two key mechanisms driving our long‐run results: (1) the cash in advance constraint on firms working capital; (2) dividends endogeneity. These two channels point in opposite directions. Lower inflation softens the cash in advance constraint and, by raising labor demand, lowers inequality. But disinflation also raises dividends and this increases inequality. The disinflation is always welfare‐improving for asset holders. We obtain ambiguous results for non‐asset holders, who suffer substantial consumption losses during the transition. ( JEL E31, E5, D3, D6)